Pelayanan Prima Terhadap Loyalitas Konsumen Schatje Kids di Bandung - luthfiyah bilqis; Ai Nunung (VALUE, 2021)
This study aims to determine the effect of excellent service on customer loyalty. The method used in this study is the associative method with a quantitative approach. The population in this study are all customers who have purchased Schatje Kids products with a sample collection of 49 respondents. The data collection technique uses primary data sources and for data processing Validity Test, Reliability Test, Normality Test, Simple Linear Analysis Test, T Test, F Test, and Coefficient of Determination Test using SPSS version 23 software. The results in this study can be concluded that Service Prima has a positive effect on Customer Loyalty which is proven by the T test where the Sig value obtained is smaller (0.000 < 0.05). The advice given by the author is expected that Schatje Kids will continue to maintain product quality and explore deeper understanding of excellent service so that consumers remain satisfied with the services that Schatje Kids provide. Keywords: Customer Loyalty, Excellent Service